Wind erosion and dust emissions in central Asia: Spatiotemporal simulations in a typical dust year. Issue 2 (18th October 2018) - Pi, Huawei; Sharratt, Brenton; Lei, Jiaqiang
Abstract: The prediction of wind erosion and dust emissions is important for controlling erosion and identifying dust sources in arid and semiarid regions of the world. This study predicts quantitatively wind erosion and dust emissions in Xinjiang Province, central Asia. The wind erosion prediction system (WEPS) was used to simulate annual soil and PM10 (particulate matter ≤10 μm in aerodynamic diameter) loss at 64 meteorological stations across the province. Soil and PM10 loss were simulated from bare surfaces at all 64 stations and from cotton and wheat fields at 11 stations. Simulated annual bare soil and PM10 loss were lowest in the Junggar (soil and PM10 loss were, respectively, 121.7 and 7.6 kg m ‐2 ) and Tarim basins (soil loss was 78.2 kg ha ‐1 and PM10 loss was 6.5 kg m ‐2 ) and highest in the Tu‐ha Basin (soil and PM10 loss were, respectively, 638.2 and 37.7 kg m ‐2 ). Stations with the highest annual soil loss in the Tarim and Tu‐ha basins also had the highest number of days with wind speeds >8 m s ‐1 . This indicated wind influenced erosion, but other factors such as soil type also affect wind erosion. The maximum monthly bare soil and PM10 loss occurred in May in the three basins, substantiating that dust storms occur most frequently during spring in the region. Simulated soil and PM10 loss were lower for cotton and wheat than bare soil, thus suggesting that maintaining vegetative cover during a portion of the year provided some protection to the soil surface from wind erosion. © 2018 John Wiley & Sons, Ltd. Abstract : Spatial and temporal variations in simulated wind erosion were found to occur across Xinjiang Province of northwest China. Variations in wind erosion were in part caused by differences in soil type and wind speed. Wind erosion was most intense during May and was lower for cropland than bare soil. Maintaining vegetative cover on the soil surface during a portion of the year is critical to protecting the soil from wind erosion.